Kepemimpinan Tim (Team Leadhership) - Nabila Padmasari; Makkiyah Makkiyah; Mochammad Isa (Pusat Riset dan Inovasi Nasional, 2023)
Team leadership is a person's ability to be able to direct, guide and coordinate its members to want to do what is directed to achieve organizational goals that have been mutually agreed upon. This study aims to understand the meaning of leadership in a team. About how leaders coordinate subordinates to achieve the goals set by the previous company. The work of a leader must be able to coordinate his subordinates so that they can work properly carrying out their responsibilities. Motivate and create a comfortable working atmosphere. About how a leader can be a good leader in leading his team. What are the obstacles a leader will face in the future? How a leader succeeds in achieving the goals to be achieved. Then there are the aspects that a leader must have. We also discuss the stages of team leadership in this article. and team leadership models.